Significance of the Error Analysis of Past Indefinite and Continuous Tenses at Secondary Level - Mumtaz, Rafy; Zahid, Zohaib; Mehmood, Hasan (Annals of Human and Social Sciences, 2024)
The present study aims to analyze the Significance of the Error Analysis of Past Indefinite and Past Continuous Tenses at Secondary Level. This study described how the students of secondary level struggle in English Grammar especially, in Past Indefinite and Past Continuous Tenses. For this purpose, all the secondary level students were selected as population of this study who were studying English as a subject and English as a Second Language in different schools of Rahim Yar Khan Pakistan. Data were collected by distributing questionnaire paper containing 10 questions of Past Indefinite and Past Continuous Tenses. Mixed Research Method was used in this research. Quantitative data were analyzed by using Statistical Package for Social Sciences (SPSS) version 20. The findings of this research study showed that a significant number of errors in Past Indefinite and Past Continuous Tenses were prevalent in secondary level students of Rahim Yar Khan.